Deep occlusal carious lesions clinical management by Brazilian dentists: a nationwide e-survey - Souza, Nayara de Oliveira; Cunha, Diana Araújo; Rodrigues, Nara Nara Sousa; Morais, Monique Marques de; Sartori, Letícia Regina Morello; Correa, Marcos Britto; Rodrigues , Flávia Pires; Saboia, Vicente de Paulo Aragão (Brazilian Dental Science, 2023)
Objective: To investigate the clinical management of deep occlusal carious lesions in permanent teeth by Brazilian dentists. Material and Methods: This cross-sectional study included a sample of 732 Brazilian dentists who responded to an electronic questionnaire composed of 20 questions addressing socio-demographic information, training and professional activity characteristics, and clinical management of deep carious lesions. Descriptive analysis was performed, considering relative and absolute frequencies and 95% confidence intervals. The association between the dentists’ variables of interest (age group, type of higher education institution, years in practice, highest academic degree completed and main sector of professional activity) and the mean number of incorrect answers regarding deep carious lesions management was analyzed by Analysis of Variance (ANOVA), followed by the Bonferroni post-test (p